Da fragmentária às mínimas: as odes de Hilda Hilst - Silva, Rivânia Maria da (2021)
This work intends to investigate how the authorship movements of the “ode” occur in different phases of Hilda Hilst’s poetics. Hence, our corpora are the books in which the writer manifests the referred lyrical form, namely, Ode fragmentária (1961), Odes maiores ao pai (1963-1966), “Ode descontínua e remota para flauta e oboé. De Ariana para Dionísio” (1974), e Da morte. Odes mínimas (1980), we list the following purposes: 1. to evidence the paths of the genre within the Hilstian lyrical universe; 2. to show the points of consistency and divergence among the writings; 3. to determine when Hilst dialogues or diverges from the classical tradition and the appropriations of a Brazilian literary model that was contemporary to her; and 4. to analyze which procedures the poet uses to modernize the ode. To fulfill the outlined objectives, we have done a theoretical-critical review of the ode, based on Ragusa (2013); Albuquerque (1936), Penna (2007), and Achcar (1994), with the intent of investigating the origins of the genre, and drawing a path on how this model came to the modern poetics, along with this, we have also discussed the interpretations done by scholars of the ode in Hilst’s poetic work.